THE ROLE OF ORGANIZATIONAL CULTURE IN THE ORGANIZATION’S ACTIVITIES (THE CASE OF JSC BANK OF GEORGIA): - Kadagishvili, Leila; Shaburishvili, Shota; Maisuradze, Rusudan (Management and Administration Journal, 2024)
The present paper provides a literature review on the concepts of organizational culture and a brief history of its development. Scientific views are analyzed according to the superficial, internal and deep levels of organizational culture. Every organization has a certain structure of its organizational culture, basic values and the values that determine its viability in everyday life. Organizational culture is a complex phenomenon and represents a pressing scientific problem, which at the moment of our research has not been properly studied in Georgia. Considering such limitations, we use the single case study method in our research, which allows us to provide an in-depth analysis of current events in a real context, to identify causal connections in the research phenomenon. This paper presents a case of a successful culture based on the example of the Bank of Georgia. The case examines the values of the organizational culture at different levels, showing how a strong, unified culture is formed in the company and how culture impacts the company’s activities. The study of the documentation depicting the functioning of the Bank of Georgia showed us that the organizational culture determines the image and reputation of the bank, ensures employee and customer satisfaction, and strengthens the reputation of the bank as the best employer.